Design and Optimization of Solar Panel Based on Sun Detector - M. Dimyati Ayatullah; Amalia Eka Rakhmania; Junaedi Adi Prasetyo (Politeknik Negeri Malang, 2022)
Many factors cause people to be reluctant to apply solar panel technology as a source of renewable electrical energy, one of which is the efficiency level of solar panels which is still very low because the position of solar panels is generally facing in one direction. In this study, we designed a tool that can automatically drive the solar panel motor according to the comparison value obtained from the LDR sensor. There are four LDR sensors for comparison that are used as a reference tool to move towards the brightest light intensity. From this solar panel, the power will be stored in the battery which at the same time drives the motor so that the rays obtained are more optimal and faster for charging the battery. From the results of the research conducted, the energy efficiency in a day is 9 percent from normal conditions without using optimization. It is hoped that this tool can help the community to use alternative renewable energy sources that are more effective and efficient.